Kinematics and Dynamics Analysis of the Push-back System of the New Split-type Six-arm Caliper Logging Tool - Tao Ren; Fei Zhang; Chunlin Zhang; Wen Sun (Jixie chuandong)
The push-back system is the main component of the well diameter measuring instrument to achieve the diameter measurement of the wellbore, the motion and dynamic characteristics are closely related to the accuracy of the logging data. In order to further improve the transmission performance of the push-back system，the closed vector polygon projection method and the matrix method are used to analyze the motion characteristics of the push-back system to open and measure the two motion states. Based on the kinematics analysis of the six-arm caliper logging tool push-back system，the dynamic statics method is used to analyze the dynamic characteristics of the two movements of the push-back system. Based on the example simulation of Adams software， the regularity curves of the displacement， velocity and acceleration of the components of the push-back system are changed with time，and the force of each component is analyzed. The motion law of the system is analyzed and verified. The theoretical design of the optimal design of the arm caliper logging tool push-back system provides a theoretical reference.